2023
DOI: 10.5194/acp-23-13255-2023
|View full text |Cite
|
Sign up to set email alerts
|

Opinion: Recent developments and future directions in studying the mesosphere and lower thermosphere

John M. C. Plane,
Jörg Gumbel,
Konstantinos S. Kalogerakis
et al.

Abstract: Abstract. This article begins with a review of important advances in the chemistry and related physics of the mesosphere and lower thermosphere (MLT) region of the atmosphere that have occurred over the past 2 decades, since the founding of Atmospheric Chemistry and Physics. The emphasis here is on chemistry, but we also discuss recent findings on atmospheric dynamics and forcings to the extent that these are important for understanding MLT composition and chemistry. Topics that are covered include observation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 256 publications
(256 reference statements)
0
4
0
Order By: Relevance
“…The charged-MSPs have also been proposed as candidates for ice nuclei, given that the charges on MSPs can effectively reduce the critical radius (rc) at low temperatures (Gumbel and Megner, 2009;Megner and Gumbel, 2009). However, the variability, distribution and charging process of MSPs remain unclear (Antonsen et al, 2017;Dawkins et al, 2023;Hervig et al, 2022;Knappmiller et al, 2011;Li et al, 2022), and this proposal has not yet gained widespread support (Duft et al, 2019;Plane et al, 2023). The mobility of electrons is much greater than that of positive ions, so MSPs in the upper mesosphere tend to collect electrons, with rocket-borne measurements showing that about 10% of MSPs are negatively charged (Plane et al, 2014;Robertson et al, 2014).…”
Section: Nucleation Processes In Pmcsmentioning
confidence: 99%
“…The charged-MSPs have also been proposed as candidates for ice nuclei, given that the charges on MSPs can effectively reduce the critical radius (rc) at low temperatures (Gumbel and Megner, 2009;Megner and Gumbel, 2009). However, the variability, distribution and charging process of MSPs remain unclear (Antonsen et al, 2017;Dawkins et al, 2023;Hervig et al, 2022;Knappmiller et al, 2011;Li et al, 2022), and this proposal has not yet gained widespread support (Duft et al, 2019;Plane et al, 2023). The mobility of electrons is much greater than that of positive ions, so MSPs in the upper mesosphere tend to collect electrons, with rocket-borne measurements showing that about 10% of MSPs are negatively charged (Plane et al, 2014;Robertson et al, 2014).…”
Section: Nucleation Processes In Pmcsmentioning
confidence: 99%
“…Fagundes et al (1996) proposed that storms do not impact the nocturnal mesosphere temperature at low latitudes. While, other researches (e.g., Plane et al, 2023;Sinnhuber et al, 2012) argued that geomagnetic storms could impact the mesosphere through ionization of the major constituents, especially at high latitudes. Unfortunately there is no events reported that storms affect the mesosphere temperature at high latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed exploration of these processes, readers are referred to the comprehensive literature (J. Plane et al (2023)).…”
Section: Introductionmentioning
confidence: 99%